Antihypertensive therapy tailored to the circadian blood pressure profile as precision medicine - Francesca Coccina; Chiara Cuccurullo; Rosa Scurti; Sante D. Pierdomenico (Hypertension Research, 2026)
Abstract Circadian blood pressure (BP) values may be different from clinic BP values. Thus, antihypertensive therapy guided solely by clinic BP might not prove appropriate. Moreover, ambulatory BP parameters are superior to clinic BP in predicting outcomes, indicating they should receive more attention as therapeutic targets. Among all relevant 24-h BP parameters, in both untreated and treated patients, two clinically unpredictable windows with proven prognostic relevance deserve attention: the period after awakening and the nighttime one. Some patients exhibit higher BP after awakening, which is associated with increased risk. In untreated patients, underdosed therapy could be started. In treated ones, most likely the drug taken the previous morning could not provide adequate duration of action. In this context, a medication with delayed onset of action and peak effect after several hours added in the evening could be of benefit to blunt morning BP rise. Others show high nighttime BP, which is associated with increased risk. In untreated patients, this can lead to prescribe underdosed therapy. In treated patients, most likely antihypertensive therapy in the morning does not cover the 24-h period. In this context, a drug with rapid onset of action and peak effect after few hours added in the evening could reduce high nighttime BP. Globally, evening therapy must be tailored to nighttime BP pattern to achieve the desired effect in the early morning or during the night. Future studies in which antihypertensive therapy is tailored to circadian BP profile, a more physiological definition of chronotherapy, should be scheduled.